(untitled) (Italian Journal of Public Health, 2005)
Traffic accidents represent an important public health issue in Italy. In order to explore the relationship between traffic accident mortality and factors such as road behaviour, vehicles and road characteristics, four different linear regression models were performed using data from the end of the 1990’s provided by the National Institute of Statistics (ISTAT) and from the Automobile Club Italia (ACI). In Italy regional differences in traffic mortality and injury rates can be observed. Strong predictors are the number of motor vehicles circulating and road length (inversely associated) and the number of new vehicles circulating and suspended driving licenses (directly associated).